2020
DOI: 10.1038/s41746-020-00328-w
|View full text |Cite
|
Sign up to set email alerts
|

Enabling precision rehabilitation interventions using wearable sensors and machine learning to track motor recovery

Abstract: The need to develop patient-specific interventions is apparent when one considers that clinical studies often report satisfactory motor gains only in a portion of participants. This observation provides the foundation for “precision rehabilitation”. Tracking and predicting outcomes defining the recovery trajectory is key in this context. Data collected using wearable sensors provide clinicians with the opportunity to do so with little burden on clinicians and patients. The approach proposed in this paper relie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 50 publications
1
75
0
2
Order By: Relevance
“…is was analogous with a prior work by Adans-Dester et al, which used eight motor tasks of Wolf Motor Function Test (WMFT) and found satisfactory results to estimate upper limb impairment and activity scales [42]. Although this was in line with our second hypothesis, the difference was small and needed to be further studied [19].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…is was analogous with a prior work by Adans-Dester et al, which used eight motor tasks of Wolf Motor Function Test (WMFT) and found satisfactory results to estimate upper limb impairment and activity scales [42]. Although this was in line with our second hypothesis, the difference was small and needed to be further studied [19].…”
Section: Discussionsupporting
confidence: 89%
“…erefore, future studies could implement other statistical models, such as machine-learning approaches, to investigate the associations between FNT kinematic variables and upper extremity motor function in individuals with stroke [42,44]. Second, this was a cross-sectional study and unable to investigate the longitudinal associations between kinematics and clinical measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In this category, systems that aim to quantify the level of correctness in executing the prescribed exercises are identified. Researchers achieved this by using popular post-stroke assessment scoring systems [65][66][67][68][69][70][71][72][73][74]:…”
Section: Clinical Assessment Emulationmentioning
confidence: 99%
“…For example, when mounted on the neck or the chest, the recordings enable detailed assessments of cardiac activity from motions of the heart and from pulsatile flow of blood through near-surface arteries, of respiratory cycles from chest wall movements, of respiratory sounds from airflow through the lungs and trachea, of swallowing behaviors from laryngeal motions and actions of the esophagus, of vocalization patterns from vocal fold activation, and of movements and changes in orientation of the core body. Distinct features in the temporal and spectral characteristics of these processes yield insights into physical activity and health status via a rich range of conventional [e.g., heart rate (HR)] ( 36 , 40 ) and unconventional (e.g., coughing frequency) metrics ( 36 , 37 , 41 43 ), in a seamless manner, without privacy concerns that would follow from use of microphones or other recording devices.…”
Section: Introductionmentioning
confidence: 99%